Pengaruh Keteladanan Guru Pendidikan Agama Kristen Terhadap Moral Siswa Kelas VIII SMP Negeri 3 Tarutung Kecamatan Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024. - Ade Mispa Anggeraini; Elisamarak Sitopu; Wilson Simanjuntak (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this research is to find out how much influence the example of Christian religious education teachers has on the morale of Class VIII students at SMP Negeri 3 Tarutung, Tarutung District, North Tapanuli Regency for the 2023/2024 academic year, with a population of all Class VIII students at SMP Negeri 3 Tarutung, Tarutung District, North Tapanuli Regency. For the 2023/2024 academic year, there are 224 Protestant Christians using a random sampling technique of 56 students. Data was collected using a closed questionnaire with 38 items compiled by the author based on variable indicators according to expert theory. The questionnaire trial was carried out on 30 Class VIII respondents at SMP Negeri 3 Tarutung, Tarutung District, North Tapanuli Regency for the 2023/2024 academic year using a 42 question questionnaire and after being tested, the results of the validity of the questionnaire trial showed that the value of rcount > rtable = 0.142-0.595 > 0.361 (there were 4 Question items that have validity less than r table = 0.361 are items number 11, 21, 27, and 32 so that the invalid questionnaire is discarded. Thus, the valid questionnaire consists of 38 questions. And the reliability of the questionnaire test is 0.896. The validity and reliability were tested. The results of data analysis showed that there was a positive and significant influence between the example of Christian Religious Education Teachers on the Morale of Class VIII Students of SMP Negeri 3 Tarutung, Tarutung District, North Tapanuli Regency for the 2023/2024 Academic Year. By testing the relationship, rcount>rttable was obtained, namely 0.479>0.226, with a significant test of the relationship between tcount > ttable, namely 4.009>2.000, coefficient of determination 22.94%. This means that H0 is rejected and Ha is accepted.